Dialectical logic for mythical and mystical superstructural systems (ii): Infinity and coincidentia oppositorum in Cusanus' thought. Issue 8 (20th May 2019) - Usó Doménech, José Luis; Nescolarde-Selva, Josué Antonio; Gash, Hugh; Segura-Abad, Lorena
Abstract : Purpose: The distinction between essence and existence cannot be a distinction in God: in the actual infinite, essence and existence coincide and are one. In it, maximum and minimum coincide. Coincidentia oppositorum is a Latin phrase meaning coincidence of opposites. It is a neo-Platonic term, attributed to the fifteenth-century German scholar Nicholas of Cusa in his essay, Docta Ignorantia . God ( coincidentia oppositorum ) is the synthesis of opposites in a unique and absolutely infinite being. God transcends all distinctions and oppositions that are found in creatures. The purpose of this paper is to study Cusanus's thought in respect to infinity (actual and potential), Spinoza's relationship with Cusanus, and present a mathematical theory of coincidentia oppositorum based on complex numbers. Design/methodology/approach: Mathematical development of a dialectical logic is carried out with truth values in a complex field. Findings: The conclusion is the same as has been made by thinkers and mystics throughout time: the inability to know and understand the idea of God. Originality/value: The history of the Infinite thus reveals in both mathematics and philosophy a development of increasingly subtle thought in the form of a dialectical dance around the ineffable and incomprehensible Infinite. First, the authors step toward it, reaching with their intuition beyond the limits of rationality and thought into the realm of the paradoxical. Then, they step back, struggling to express their insight within the limited scope of reason. But the Absolute Infinite remains, at the border of comprehensibility, inviting them with its paradoxes, to once again step forward and transcend the apparent division between finite and Infinite.